(untitled) (Wire Insights: Journal of Innovation Insights, 2023)
This article explores the importance of adequately preparing future teachers to model modern lessons. The focus is on developing the skills and knowledge necessary for effective lesson planning, incorporating contemporary teaching methodologies, and integrating technology for enhanced learning experiences. The article provides a literature analysis, discusses various methods for teacher preparation, presents results from successful implementations, and concludes with suggestions for further improvements in teacher education programs.